Dendritic α-Fe2O3/TiO2 nanocomposites with improved visible light photocatalytic activity. Issue 13 (14th March 2016) - Li, Xin; Lin, Huiming; Chen, Xiang; Niu, Hao; Liu, Jiuyu; Zhang, Ting; Qu, Fengyu
Abstract : A branch-like α-Fe2 O3 /TiO2 heterostructure has been synthesized controllably through an electrospinning method combined with a hydrothermal approach. Abstract : The design and synthesis of unique novel heterostructures for high-performance photocatalytic activity has exerted a tremendous fascination and has recently attracted intensive attention. In this work, a branch-like α-Fe2 O3 /TiO2 heterostructure has been synthesized controllably through an electrospinning method combined with a hydrothermal approach. The backbone of the heterostructure is composed of a 3D porous TiO2 nanofiber (∼70 nm in diameter) network with plenty of α-Fe2 O3 nanorods (100–200 nm in length) deposited on them. The novel branch-like nanocomposites have an abundantly porous structure as well as large surface areas (up to 42.8 m 2 g −1 ). In addition, their visible light photodegradation behaviour towards organic dyes, including Congo red (CR), methylene blue (MB), eosin red (ER) and methyl orange (MO), was investigated. Their excellent photocatalytic performances are attributed to their large surfaces, improved visible light absorption and high separation efficiency of the photogenerated electrons/holes. Furthermore, the degradation process was further studied by varying the amount of α-Fe2 O3 deposited. The sample α-Fe2 O3 /TiO2 -3 possessed the best performance to efficiently decolor CR solution even at a high concentration of 50 mg L −1 (160 min, 94 mg g −1 ), ascribed to the high adsorption capacity derived from the large surface, strong electrostatic interaction and structural match between α-Fe2 O3 /TiO2 -3 and CR. These α-Fe2 O3 /TiO2 heterostructures exhibit great potential for decontamination of organic pollutants in waste water under visible light.